2019
DOI: 10.3390/risks7030077
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy Risk, Its Financial Determinants and Reporting Delays: Do Managers Have Anything to Hide?

Abstract: The aim of this study was to investigate whether firms’ reporting delays are interconnected with bankruptcy risk and its financial determinants. This study was based on 698,189 firm-year observations from Estonia. Annual report submission delay, either in a binary or ordinal form, was used as the dependent variable, while bankruptcy risk based on an international model or the financial ratios determining it were the independent variables. The findings indicated that firms with lower values of liquidity and ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 62 publications
3
49
0
3
Order By: Relevance
“…However, one should note that one of the most common reasons that lead to a corporate failure is poor financial risk management and bad debt management (Kristanti et al, 2019). Researchers also agree that the main determinants of bankruptcy risk are liquidity, profitability and leverage, and these factors are in turn widely used as variables in a variety of bankruptcy forecasting models (Lukason & Camacho-Miñano, 2019). The complex view on important financial ratios influencing the stable development of enterprises and thus the financial health and competitive position is presented in the previous papers (Kovacova et al (2019); Pointer & Khoi, 2019;Kliestik et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, one should note that one of the most common reasons that lead to a corporate failure is poor financial risk management and bad debt management (Kristanti et al, 2019). Researchers also agree that the main determinants of bankruptcy risk are liquidity, profitability and leverage, and these factors are in turn widely used as variables in a variety of bankruptcy forecasting models (Lukason & Camacho-Miñano, 2019). The complex view on important financial ratios influencing the stable development of enterprises and thus the financial health and competitive position is presented in the previous papers (Kovacova et al (2019); Pointer & Khoi, 2019;Kliestik et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is essential to include information other than financial ratios in the prediction models. The first possibility is to use reporting delays, as it has been shown that firms in poor financial situation often engage in the unethical behaviour of delaying financial information (Altman et al 2010;Lukason 2013;Lukason and Camacho-Miñano 2019). Still, the pre-default timeframe could be too short for a lengthy violation behaviour to occur.…”
Section: Loan Payment Default In the Context Of Firm Failurementioning
confidence: 99%
“…In their study based on Estonian firms, Lukason and Andresson (2019) showed that up to one year prior to bankruptcy, the prediction model using tax arrears has clearly better failure-prediction capabilities than the model using financial ratios, while the best results were obtained by combining financial information with tax arrears. Additionally, several studies have previously focused on non-compliance with regulations, indicating a clear link between late filing or non-submission of accounts with increased risk of financial distress and business failure (Altman et al 2010;Lukason 2013;Lukason and Camacho-Miñano 2019).…”
Section: The Articles In Tablementioning
confidence: 99%
“…There are many studies on the causes of bankruptcy, including attempts by managers to hide information in financial statementsin Estonia (Lukason, Camacho-Minano 2019).…”
Section: Literature Reviewmentioning
confidence: 99%